Disharmony in Regulations Concerning the Settlement of Criminal Cases Using a Restorative Justice Approach in the Criminal Justice System - Dewi Retna Martani; Jeffry A. Ch. Likadj; Orpah G. Manuain (Asosiasi Dosen Muda Indonesia, 2026)
This study examines the regulations governing the mechanism for resolving criminal cases through a restorative justice approach from the perspectives of Police Regulations (PERKAP), Prosecutor Regulations (PERJA), and Supreme Court Regulations (PERMA). The legal issue raised in this research concerns the overlapping norms regulating the mechanism for resolving criminal cases using a restorative justice approach. The formulation of the problems in this study are: how criminal case resolution through a restorative justice approach is viewed within these three regulations, and how the implementation of restorative justice is reviewed based on the Theory of Justice. The purpose of this research is to analyze the resolution of criminal cases through a restorative justice approach from the perspectives of PERKAP, PERJA, and PERMA, as well as to analyze the implementation of restorative justice based on the theory of justice. The results of the study reveal that the implementation of restorative justice within the perspectives of these three regulations experiences contradictions in terms of resolving criminal cases through a restorative justice approach. From the perspectives of PERKAP and PERJA, the resolution of criminal cases through restorative justice may be terminated if the restorative justice requirements as stipulated in PERKAP and PERJA have been fulfilled. Meanwhile, from the perspective of PERMA, the resolution of criminal cases through a restorative justice approach is not intended to eliminate criminal liability. This means that even if the restorative justice requirements between the victim and the perpetrator have been fulfilled during the trial process, the judge may continue the examination and the resolution may ultimately end with a judicial decision.